Project management 2.0 : leveraging tools, distributed collaboration, and metrics for project success - Kerzner, Harold (Wiley, 2015)
Get connected and improve outcomes with a more modern approach to project management Project Management 2.0 tackles the new emerging approach and toolset for practicing project management in a virtual world. Author Harold Kerzner is recognized as the thought leader in project management, and in this book, he shows how PM 2.0 offers better outcomes with a focus on new tools, better governance, improved collaboration, and more meaningful reporting using KPIs, metrics, and dashboards. This full color guide explores the impact PM 2.0 changes are having on organizations around the world, and provid.